Transformational Leadership of Nurse Managers Enhances Healthcare Service Quality Through a Strengthened Nursing Organizational Culture - Khoirul Amin Subhakti; Catharina Dwiana Wijayanti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The transformational leadership style of the ward head plays a strategic role in shaping a nursing organizational culture that supports high‑quality healthcare services. This study aims to examine empirical evidence on the influence of the ward head’s transformational leadership style on nursing organizational culture, with a particular focus on three key outcomes: professionalism, workplace spirituality, and nurses’ work effectiveness. The review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. From a total of 233 identified records, 16 articles met the inclusion criteria. The literature search was performed using the PICOT framework across the PubMed, Gale OneFile, and ProQuest databases, employing the keywords “transformational leadership” AND “head nurse”. The findings demonstrate that the ward head’s transformational leadership exerts a significant influence on nursing organizational culture. This leadership style enhances nurses’ professionalism by strengthening clinical autonomy, ethical competence, clinical leadership, and creativity. Furthermore, transformational leadership fosters workplace spirituality by increasing the meaning of work, psychological well‑being, caring values, and perceptions of organizational justice. These improvements subsequently contribute to greater work effectiveness, reflected in enhanced nurse performance, higher quality of nursing care, improved patient safety, stronger nurse retention, and greater organizational sustainability. Nursing organizational culture is shown to function as a key mediator that links transformational leadership to these diverse outcomes. This scoping review confirms that the transformational leadership style of the ward head constitutes a crucial managerial strategy for cultivating a professional, meaningful, and effective nursing organizational culture, with direct implications for improving the overall quality of healthcare services.Keywords: transformational leadership; ward head; nursing organizational culture; professionalism; workplace spirituality; work effectiveness